A Survey on various Clustering Algorithms in Wireless Sensor Network - Singh, Karampal; Attri, Varinder (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless Sensor Network has gained the attention of scientists and researchers because of its potential for applications in various fields of science and technology and is one of the most rapidly advancing technologies. Wireless sensor network faces some severe resource and computational constraints due to which their implementation becomes a difficult task. Among the resource constraints, the major challenge for WSN is energy limitation. Energy efficient algorithms must be implemented so as to prolong the lifetime of network. Network lifetime can be maximized through clustering algorithms, where cluster is responsible for sending the data to the base station and not all the nodes are involved in transmission of data. In this paper, we summarized various clustering algorithms for WSNs and draw comparison between them based on clustering properties, cluster head capability and clustering process and briefly discuss types of clustering as well as discuss various performance metrics, challenges and issues faced during the formation of cluster head.